STRATEGI PENGEMBANGAN URBAN FARMING “BURUAN SAE” MANG ODED DI KELURAHAN LINGKAR SELATAN KECAMATAN LENGKONG KOTA BANDUNG - Hanifah, Mariska Nur; Perdana, Tomy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
“Buruan SAE" Mang Oded is one of the "Buruan SAE" urban farming groups as a program promoted by the Bandung City Agriculture and Food Security to solve the problem of food availability. In its development, "Buruan SAE" Mang Oded faced obstacles, there are the lack of community participation and the stagnation of the business development. This study aims to identify internal and external factors that influence the development of Mang Oded's "Buruan SAE" and determine the right development strategy. The research design used is descriptive qualitative research. The data collection method were carried out though interviews, observation, and documentation with the decision makers at “ Buruan SAE” Mang Oded. The analytical tools used in this study are the IFE, EFE, IE, SWOT and QSPM matrix. Based on the calculation results, the total score of the IFE matrix is 2.843 and the total score of EFE matrix is 3.066 which indicates that the group's internal and external factor conditions are above average. The group's current position based on the IE matrix is in cell II, which is the Growth and Build strategy. Based on the SWOT matrix, four alternative strategies are obtained which are then analyzed using the QSPM, there are: (1) Utilizing social media and creating the new innovations, (2) Optimizing land use, (3) Using special labels or brands on products and develop the type of product, and (4) Maintaining market and cooperative relations with the government.